Viral modernism : the influenza pandemic and interwar literature - Outka, Elizabeth (Modernist latitudes., 2020)
"The influenza pandemic of 1918-1919 took the lives of between 50 and 100 million people worldwide, and the United States suffered more casualties than in all the wars of the twentieth and twenty-first centuries combined. Yet despite these catastrophic death tolls, the pandemic faded from historical and cultural memory in the United States and throughout Europe, overshadowed by World War One and the turmoil of the interwar period. In Viral Modernism, Elizabeth Outka reveals the literary and cultural impact of one of the deadliest plagues in history, bringing to light how it shaped canonical works of fiction and poetry. Outka shows how and why the contours of modernism shift when we account for the pandemic's hidden but widespread presence. She investigates the miasmic manifestations of the pandemic and its spectral dead in interwar Anglo-American literature, uncovering the traces of an outbreak that brought a nonhuman, invisible horror into every community. Viral Modernism examines how literature and culture represented the virus's deathly fecundity, as writers wrestled with the scope of mass death in the domestic sphere amid fears of wider social collapse. Outka analyzes overt treatments of the pandemic by authors like Katherine Anne Porter and Thomas Wolfe and its subtle presence in works by Virginia Woolf, T.S. Eliot, and W.B. Yeats. She uncovers links to the disease in popular culture, from early zombie resurrection to the resurgence of spiritualism. Viral Modernism brings the pandemic to the center of the era, revealing a vast tragedy that has hidden in plain sight"--